Classification of gross motor function in children with cerebral palsy from a highly specialized pediatric institution in Peru - Valdivia-Loro, Jean Pierre (2023)
Objective: To determine the level of gross motor function classification in children with cerebral palsy at Instituto Nacional de Salud del Niño San Borja (INSN SB). Materials and methods: Descriptive study comprising 51 pediatric patients from 1 to 16 years of age, diagnosed with cerebral palsy according to the International Classification of Diseases version 10, in the period 2021. The Gross Motor Function Classification System (GMFCS) and Gross Motor Function Measurement (GMFM) instruments were used for their evaluations. Results: Of the patients evaluated, 58.8% (n=30) were male and 41.2% (n=21) female, of whom 66.7% (n=34) were from Lima and 33.3% (n=17) from the provinces. The age group 2-4 years concentrated the highest number of cerebral palsy with 33.3% (n=17), compared to the rest. According to the type of cerebral palsy, 64.7% (n=33) presented spastic quadriplegic type, 29.4% (n=15) unspecified and 5.9% (n=3) athetoid. According to the GMFCS, 39.2% (n=20) presented level V, 21.6% (n=11) level I, followed by level II and IV, and finally level III. Conclusions: The study demonstrates that the spastic quadriplegic cerebral palsy type is the most frequent, as well as level V according to GMFCS.